Thyroid hormone as a clinical predictor in acute exacerbation of COPD: Relationship with %FEV1, exacerbation severity, and hospital stay duration - Yanuar; Apriningsih, Hendrastutik; Setijadi, Ana Rima; Reviono; Adhiputri, Artrien (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of mortality worldwide. Acute Exacerbations of COPD (AECOPD) significantly impact patient outcomes and healthcare costs. Thyroid hormone dysregulation has been proposed as a potential systemic effect of AECOPD. However, the relationship between thyroid hormones and AECOPD clinical predictors, such as %FEV1, exacerbation severity, and hospitalization duration, remains unclear.Objective: This study aimed to investigate the relationship between thyroid hormones and key clinical predictors in patients with Acute Exacerbation of COPD (AECOPD), including %FEV1, exacerbation severity, and Length of Stay (LOS).Method: This is a cross-sectional study which included 32 patients admitted for AECOPD from November 2023 to January 2024 at Sebelas Maret University Hospital. Thyroid function was assessed by measuring serum levels of Thyroid-Stimulating Hormone (TSH), Free Triiodothyronine (FT3), and Free Thyroxine (FT4). We evaluated the association between thyroid hormone levels and Forced Expiratory Volume in 1 second (FEV1), severity of exacerbation, and Length of Stay (LOS).Results: The study found a significant positive correlation between FT3 and %FEV1 (r=0.414, p=0.019), indicating a relationship between higher FT3 and better lung function. A significant negative correlation was observed between FT3 and exacerbation severity (r=-0.506, p=0.003), then FT3 and LOS (r=-0.350, p=0.050). FT4 also negatively correlated with exacerbation severity (r=-0.367, p=0.039). The optimal cut-off for FT3 to predict severe exacerbation was <2.65 pmol/L, with a sensitivity of 80.8% and specificity of 100%.Conclusion: The study indicates a significant relationship between thyroid hormones, particularly FT3, and clinical outcomes in AECOPD patients. These findings suggest that thyroid hormone assessment could be useful in predicting the severity of acute COPD exacerbations, contributing to more targeted management strategie.